COLON-TARGETED CYCLOSPORINE IN THE IL10 KNOCK OUT MODEL OF CROHN'S COLITIS. (8th June 2013) - Coulter, I S; Aversa, V; Taylor, C T; Fallon, P
Abstract : Introduction: Cyclosporine A (CyA) is a powerful immunosuppressive agent and has been used off label for steroid-dependent or steroid-refractory ulcerative colitis. However, systemic exposure results in a number of side effects. A novel advanced oral drug delivery system, SmPill ®, has been developed to permit targeted release of CyA directly into the colon tissue with limited systemic exposure. Aims/Background: The objective was to compare SmPill ® -CyA activity in the IL10 knock-out mouse model of Crohn's colitis against the marketed Neoral ® (po) and Sandimmun ® (ip). Method: Mice were treated for 42 days, received the equivalent of 15 mg/kg/day CyA as well as untreated and SmPill ® placebo. A secondary objective was to measure systemic pro-inflammatory cytokine activity in isolated spleen cells. Results: General Mouse Health: The SmPill ® -CyA group were significantly heavier than mice in all other groups on Day 42. The SmPill ® -CyA group had the lowest Disease Activity Index scores relative to the other groups. Colon Tissue Inflammatory Biomarkers: The untreated mice had the highest Serum Amyloid A levels (SAA), with the lowest levels seen with those treated with SmPill ® -CyA (p<0.001) followed by Sandimmun ® (i.p) (p<0.01) treated mice. Sandimmun (i.p) and SmPill ® -CyA groups had significantly lower (P<0.01) histology scores relative to Neoral ® . Neoral ® (po) had the greatest relative score. The highest levels of Myeloperoxidase (MPO) activity were seen in the untreated and placebo mice. There was statistically lower MPO activity in both the SmPill ® -CyA and Sandimmune ® (i.p.) groups relative to untreated mice (p<0.05). Similarly to a reduction in MPO activity, the SmPill ® -CyA groups also had reduced IL-1α, IL-17 and TNFα pro-inflammatory cytokine levels (p<0.05) in colon tissue at Day 42. Systemic Tissue Inflammatory Biomarkers: In a measure of systemic CyA activity, the activity of a number of pro-inflammatory cytokines in activated isolated spleen cells was measured. The Sandimmune ® (i.p) treated mice had significantly reduced production of TNF-α (p<0.01) and IL-17 (p<0.05) relative to cells from the untreated and placebo treated mice. In mice treated with SmPill ® -CyA the reduction in TNF-α and IL-17 release by cells was non-significant. The pro-inflammatory cytokine expression levels for Neoral ® was between that of Sandimmune ® and SmPill ® -CyA. Conclusion: The above study demonstrated that SmPill ® -CyA conferred preferential local colonic efficacy with limited systemic activity, in effect, harnessing the local efficacy of CyA and reducing systemic side effect risks. A SmPill ® -CyA formulation, CyCol ®, has progressed through human Phase I (PK) study in Canada and Phase IIb study in Ireland and the UK. A multi-centre Phase IIb study is being planned.